2015
DOI: 10.1108/nfs-05-2015-0058
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional and therapeutic potential ofbael(Aegle marmelosCorr.) fruit juice: a review

Abstract: Purpose – The purpose of this paper is to summarize the scientific information of various qualities of bael fruit juice used in traditional system of medicine for variety of purposes. Utilization of bael fruit juice in day-to-day life has great nutritional, therapeutic, and commercial importance. Bael fruit contains nutrients like vitamins (riboflavin), minerals, trace elements, energy and phytochemicals, including flavonoids, polyphenols and antioxidants, that have been shown to have varied he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 50 publications
0
28
0
Order By: Relevance
“…Studies have reported that Aegle marmelos exhibits anti-viral effect [ 20 ], inhibitory effect against Ehrlich ascites carcinoma [ 21 ], anti-hyperglycemic effect [ 22 , 23 ], anti-adipogenic effect [ 24 ], anti-diarrhoeal effect [ 25 ], chemo-modulatory effect against DMBA-induced skin tumorigenesis [ 26 ], ameliorative effect against alloxan-induced diabetic cardiomyopathy [ 27 ], radioprotective effect [ 28 ], anti-oxidant and hepatoprotective effects [ 29 ]. In addition, consumption of unripe and half ripe Aegle marmelos helps in complete digestion of food, prevents scurvy and has anti-microbial activity against pathogenic intestinal microorganism [ 30 ]. Nyctanthes arbor-tristis (common name – night flowering jasmine) exhibits anti-inflammatory effect [ 31 ], anti-amoebic activity, anti-leishmanial activity, anti-viral activity [ 32 ], analgesic activity, anti-pyretic activity and ulcerogenic activity [ 33 ], anti-oxidant activity [ 34 , 35 ], hypoglycemic activity, and hypolipidemic activity [ 36 ] in vitro studies.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have reported that Aegle marmelos exhibits anti-viral effect [ 20 ], inhibitory effect against Ehrlich ascites carcinoma [ 21 ], anti-hyperglycemic effect [ 22 , 23 ], anti-adipogenic effect [ 24 ], anti-diarrhoeal effect [ 25 ], chemo-modulatory effect against DMBA-induced skin tumorigenesis [ 26 ], ameliorative effect against alloxan-induced diabetic cardiomyopathy [ 27 ], radioprotective effect [ 28 ], anti-oxidant and hepatoprotective effects [ 29 ]. In addition, consumption of unripe and half ripe Aegle marmelos helps in complete digestion of food, prevents scurvy and has anti-microbial activity against pathogenic intestinal microorganism [ 30 ]. Nyctanthes arbor-tristis (common name – night flowering jasmine) exhibits anti-inflammatory effect [ 31 ], anti-amoebic activity, anti-leishmanial activity, anti-viral activity [ 32 ], analgesic activity, anti-pyretic activity and ulcerogenic activity [ 33 ], anti-oxidant activity [ 34 , 35 ], hypoglycemic activity, and hypolipidemic activity [ 36 ] in vitro studies.…”
Section: Introductionmentioning
confidence: 99%
“…During the past few decades, a spike in its cultivation as a horticulture plant has been attributed to its medicinal properties, along with a hardy nature that allows it to be cultivated on marginal lands with acidic or alkaline soils [5,6]. The traditional medicine system of Ayurveda in India routinely uses every part of A. marmelos as a therapy for medical conditions [7,8]. The leaves are most easily accessible, and are therefore more regularly used for the treatments than any other plant part.…”
Section: Introductionmentioning
confidence: 99%
“…The ripe fruit juice is aromatic, has cooling and laxative effects, and arrests secretion or bleeding. [4] Research studies confirm that the plant is rich in aegelin, marmelin, fagarine, marmesin, betulinic acid, auroptene, marmelosin, imperatorin, and limonene. [5] O. indicum L. Benth.…”
Section: Original Articlementioning
confidence: 95%